Arsenic and cadmium accumulation in rice and mitigation strategies - Zhao, Fang-Jie; Wang, Peng (Plant and soil, 2020)
Background Arsenic (As) and cadmium (Cd) are two toxic elements that have a relatively high risk of transfer from paddy soil to rice grain. Rice is a major dietary source of these two elements for populations consuming rice as a staple food. Reducing their accumulation in rice grain is important for food safety and human health. Scope We review recent progress in understanding the biogeochemical processes controlling As and Cd bioavailability in paddy soil, the mechanisms of their uptake, translocation and detoxification in rice plants, and strategies to reduce their accumulation in rice grain. Similarities and differences between the two elements are emphasized. Some knowledge gaps are also identified. Conclusions The concentrations of As and Cd in rice grain vary by three orders of magnitude, depending on the bioavailability of the two elements in soil, rice genotype and growing conditions. The redox potential in paddy soil has a profound but opposite effect on As and Cd bioavailability, whereas soil pH affects Cd bioavailability more than As bioavailability. A number of key genes involved in As and Cd uptake, translocation, sequestration, and detoxification in rice have been characterized. Allelic variations of several genes underlying the variations in Cd accumulation have been identified, but more remains to be elucidated, especially for As. Two types of strategies can be used to reduce As and Cd accumulation, reducing their bioavailability in soil or their uptake and translocation in rice. Reducing the accumulation of both As and Cd in rice simultaneously remains a great challenge.